Genetic diversity of native chicken based on analysis of D-Loop mtDNA marker - Tike Sartika; D Duryadi; S.S Mansjoer; B Gunawan (Indonesian Center for Animal Research and Development (ICARD), 2000)
Production was carried out using control region/D-loop mtDNA marker. The base population of native chicken was selected from subpopulation at Cianjur, Jatiwangi, Depok, Bogor I, and Bogor 2. Samples from each population was 10 heads and 2 samples Green Jungle Fowl (Gallus various) from East Java as out Group samples. Two primers binding conserved tRNA Phenylalanine gene and tRNA Glutamine gene were DNA Heavy stranded HI255 (5'-CATCTTGGCATCTTCAGTGCC-3') and DNA Light stranded Ll6750 (5'-AGGACTACGGCTTGAAAAGC-3') was used to amplify D-Ioop mtDNA chicken. PCR-RFLP methods with 6 restriction enzymes 4 cutter such as, Alul (AG↓CT), Hpall (C↓CGG), Mbol (↓GATC), Rsal (GT↓AC), NlaIII (CATG↓) and HaeIII (GG↓CC) were used to detect polymorphism within and between subpopulation. Result of experiment show that mtDNA which was amplified by PCR was 1320 bp, consist of 1227 bp control region/D-loop, 45 bp tRNA Glutamine gene and 48 bp tRNA Phenylalananine gene. PCR product which were digested from 6 endonucleases enzyme show that native chicken within and between population was monomorphic and if its compare with Green Jungle Fowl was polymorphic. Key words: Native chicken, genetic diversity, mtDNA